UPAYA MANAJEMEN KESISWAAN DALAM MEMBENTUK KARAKTER ISLAMI - Muhammad Fadholi; Nurul Latifatul Inayati (PAI RAFAH, 2023)
Schools are used as a place to improve one's achievements and develop the quality of life when facing the future. To carry out its activities, the school must have student management, curriculum management, and so on, so that the school can improve its quality. This journal discusses student management efforts in shaping Islamic character at SMP Muhammadiyah 5 Surakarta which has the aim to (1) Describe student management planning in shaping the Islamic character of students at SMP Muhammadiyah 5 Surakarta. (2) Describe the implementation of student management in shaping the Islamic character of students at SMP Muhammadiyah 5 Surakarta. The type of research conducted. The type of data analysis used is field data analysis. In collecting data, interviews, observation, and documentation methods were used. The data analysis method used in this research is descriptive analysis which is used to translate a situation from general to specific. The results of research findings at SMP Muhammadiyah 5 Surakarta, and the efforts made at SMP Muhammadiyah 5 Surakarta start from the planning process, acceptance to the learning process in which there is planning, implementation, evaluation, and reporting. The character-building process at Muhammadiyah 5 Karanganyar Junior High School includes the 5S Program (Smile, Greeting, Greeting, Polite and Courteous), Habituation of Dhuha Prayers, Morning Tadarus, Dzuhur Prayers in Congregation.